A study on the oral health status, knowledge, attitudes and practices on dental health of senior students of the different branches of the UP Health Sciences - De Leon, Arturo P.
The paper revolves around the study conducted by the clinician to assess the oral health status and to evaluate the extent to which other future members of the health team know about matters on dental health. A representative sample of 40 respondents was drawn from the universal population of 273 senior students of the different branches of the U.P. Health Sciences the College of Medicine, College of Nursing, the College of Pharmacy, the Institute of Applied Medical Profession. An actual oral examination of the respondents and a survey using a questionnaire were conducted to gather the necessary data. Based on the results obtained, it was found out that senior students of the U.P. Health Sciences express good attitudes towards dental health, have acceptable dental health practices, but their knowledge on dental health needs much improvement.